International public goods : incentives, measurement, and financing - Ferroni, Marco A., 1948-; Mody, Ashoka; World Bank. (Boston, MA Kluwer Academic Publishers : Washington, DC. World Bank, 2002)
This book focuses on the strategic and practical challenges of fostering solutions that have the character of international public goods, paying particular attention to the financing of these goods. It usefully identifies a range of international public goods and explores the possibilities and prospects for increasing their supply.
Machine generated contents note: 1. Global Incentives for International Public Goods: -- Introduction and Overview -- Marco Ferroni and Ashoka Mody -- 2. Defining International Public Goods: Conceptual Issues -- Oliver Morrissey, Dirk Willem te Velde, and Adrian Hewitt -- 3. Supplying International Public Goods: -- How Nations Can Cooperate -- Scott Barrett -- 4. Financing International Public Goods -- Todd Sandler -- 5. Allocating Aid to International Public Goods -- Dirk Willem te Velde, Oliver Morrissey, and Adrian Hewitt -- 6. Regional Public Goods in Official Development Assistance -- Marco Ferroni.
Includes bibliographical references and index.
rua 19/09/14
Loans
Keywords: Public goods -- International cooperation; International economic relations